Romance Etymology: Tendencies and Prospects - I. I. Chelysheva (Научный диалог)
The article is devoted to the methodology, theory and practice of etymological research in Romance linguistics. The paper presents general regularities of the construction of the Romance etymological dictionaries and the main directions in the modern Romance etymology. The relevance of the work is determined by the special importance of etymology for the Romance languages, which origin and development is well documented, as well as by the limited use of Romance material outside the circle of novelists. Special attention is paid to dictionaries of French and Italian languages. The novelty of the study is due to the fact that the paper identifies the main lines of development of modern etymological studies both in retrospect and in prospect. The article shows how the etymological method that establishes the origin of the word and the historical analysis that recreates the history of the word are combined in the application to the Romance languages, as well as how the phonetic, morphological and semantic components are correlated in the etymological study.